Menangani Kesulitan Belajar Menulis (Disgrafia) dengan Menggunakan Media Kartu Kata atau Kartu Ejaan Bergambar - Widyanti, Aprilia Nur; Handayani, Arri; Rakhmawati, Dini (STKIP Andi Matappa Pangkep, 2024)
Learning difficulty is a condition experienced by students in learning which is characterized by certain obstacles to achieving the expected learning outcomes. In the learning process, both teachers and students certainly expect to achieve maximum learning goals and learning outcomes. In reality, these expectations are not always realized, there are still many students who do not achieve the expected learning outcomes. The causes of learning difficulties experienced by students can come from internal factors and external factors. This is a challenge that is always faced by teachers. Teachers play a role in helping to solve the problem of learning difficulties faced by students. One of the learning difficulties that students often experience is learning to write (dysgraphia). This literature review aims to help teachers understand and help students who have difficulty learning to write (dysgraphia). The method used is a literature study by reviewing relevant articles from 2019-2024. To handle learning difficulties in writing (dysgraphia) teachers can use word cards or picture spelling cards. In using word card learning media or picture spelling cards, teachers should always provide motivation, enthusiasm, and special attention to students who have difficulty learning to write.